THE PARADOX OF TRADITION AND MODERNITY: THE DYNAMIC TRANSFORMATION OF INDONESIAN PESANTREN - Erna Nur Komariah; Nur Wakhdatun Maolla; Amin Basir (ASIAN PUBLISHER, 2025)
The transformation of Indonesian pesantren in the era of globalization presents a complex challenge between preserving tradition and embracing modernity. This study aims to explore the paradoxical dynamics between maintaining pesantren’s traditional values and the demands of Islamic educational modernization. A qualitative descriptive approach through library research was employed, utilizing academic journals, books, and official documents published between 2015 and 2024. Content analysis was conducted on theories of educational modernization, pesantren cultural identity, and institutional responses to global change. The findings reveal that pesantren are actively transforming through curriculum integration, technology adoption, and institutional management development, while preserving religious traditions and the authority of kyai. The paradox of tradition and modernity emerges not as a barrier but as a unique strength in shaping globally relevant yet locally rooted Islamic education.